Effect of topical magnesium sulfate in latent phase on Bishop Score and latent phase duration in primiparous women - Arezoo Heydari; Farzaneh Nasiri; Nourossadat Kariman (Mashhad University of Medical Sciences, 2020)
Introduction: As the active phase of labor, prolongation of the latent phase is associated with risks for the mother and fetus. Cervical status, determined by Bishop's score, is one of the factors that influence the duration of the latent phase. This study was performed with aim to determine the effect of topical magnesium sulfate in latent phase on Bishop Score, latent phase duration and delivery outcomes in primiparous women. Methods: This double-blind clinical trial study was conducted on 60 nulliparous women in Izadi hospital of Qom in 2018. The participants were randomly divided into two groups of magnesium sulfate and placebo (n=30 in each group). Before the intervention, vaginal examination was performed and Bishop's score was calculated. If Bishop's score was less than 5, the individual would be included in the study. In the intervention group, 10cc of magnesium sulfate 50% was administered during the examination and in the control group, 10 cc distilled water were poured on the cervix. Vaginal examination was done every 4 hours. Finally, the Bishop scores, duration of latent phase, and overall duration of latent phase until delivery were calculated and compared in the two groups. Data were analyzed by SPSS software (version 24) and Chi-square, Fisher, Independent t, and Mann-Whitney tests. P<0.05 was considered statistically significant. Results: Before the intervention, there was not significantly different between the two groups in mean Bishop score (p= 0.554). However, in subsequent examinations which were done 4 (p=0.001) and 8 (p=0.001) hour after the intervention, these differences were significant. Duration of latent phase in the intervention group was 636.87± 455.55 minutes and in the control group was 1209.17±688.52 minutes (p=0.004). Also, the total duration of labor was 1032.54±585.20 minutes in the intervention group and 1524.28±531.99 minutes in the control group (p=0.001). Two groups had no significant difference in terms of other delivery outcomes (p≥0.05). Conclusion: The use of topical magnesium sulfate at the beginning of the latent phase improves Bishop's score, thereby shortening the latent phase duration and subsequently shortening the labor duration.